2014
DOI: 10.1097/mpa.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Poor Analgesic Efficacy of Epidural Analgesia in Critical Care Patients After Pancreaticoduodenectomy

Abstract: Premature epidural abortion rate was high and associated with analgesic morbidity. Pain score was predictive of epidural abortion. Thus, preference toward epidural analgesia cannot be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The study cohorts were largely comparable regarding sex, age and ASA grade, except one study 7 in which patients in the N-EA group had a higher ASA grade. The types of EA infusion were: patient-controlled (1) 23 , continuous infusion (5) 4,5,7,20,25 , patient-controlled and continuous infusion (1) 21 , and no information regarding infusion (4) 3,14,22,24 . The EA protocols warranted termination between POD 3 and 6 (4 studies did not provide information on duration of EA).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study cohorts were largely comparable regarding sex, age and ASA grade, except one study 7 in which patients in the N-EA group had a higher ASA grade. The types of EA infusion were: patient-controlled (1) 23 , continuous infusion (5) 4,5,7,20,25 , patient-controlled and continuous infusion (1) 21 , and no information regarding infusion (4) 3,14,22,24 . The EA protocols warranted termination between POD 3 and 6 (4 studies did not provide information on duration of EA).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 3,5,7,23 reported on treatment failure of EA, which occurred in 121 (28⋅5 per cent) of 425 patients (range between studies 14⋅8-55⋅6 per cent). The reason for EA treatment failure was specified in 111 patients in three studies 5,7,23 : 49 (44⋅1 per cent) due to haemodynamic compromise, 47 (42⋅3 per cent) to inadequate pain control and 15 (13⋅5 per cent) to catheter migration or malfunction. In the study 20 that looked at EA and paravertebral catheters, two patients (8⋅7 per cent) receiving EA but none who had paravertebral catheter treatment required intervention for hypotension, although it was unclear whether this led to treatment failure.…”
Section: Treatment Failure Of Initial Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…36 The most used alternative for EA is the patient-controlled analgesia with intravenous morphine (ivPCAM). 3,5,7…”
Section: Introductionmentioning
confidence: 99%